Principal Strategies to Improve Teachers' Pedagogic Competence in The Digital Era - Hasanah, Siti Nur Aviatun; Yaqin, Muhammad Ainul (Al-Qalam Institue, 2025)
This study aims to analyze the role of school principals in improving teachers’ pedagogical competence in the digital era through a visionary and instructional leadership. Pedagogical competence is a fundamental foundation for professional educators, particularly in addressing learning dynamics in the digital age, which demands adaptive, innovative, and transformational skills. This research uses a case study with a qualitative method to explore the processes and strategies applied to enhance teachers’ pedagogical competence. The findings show that principals play a strategic role by implementing various techniques, such as educational technology training, ongoing supervision, digital infrastructure provision, and strengthening collaboration in professional learning communities. However, challenges like low digital literacy and resistance to change remain obstacles. The implications of this study highlight that the success of digital education transformation depends not only on technology but also on the quality of human resources, especially teachers, in managing learning professionally and reflectively.